The Relationship between the Customers’s Joy and the Emotional Interaction and Marketing - Abu Gnem, Azhar Nema (Opción, 2019)
The study aims to reveal the relationship and influence between the emotional interaction of the faculty member through its sub-dimensions and the customer's delight. For the purpose of analysis and statistical analysis, the study relied on empirical analysis. The study has reached several results, the most important of which is the interest of female teachers in private schools. In conclusion, the greater the interest and the use of emotional interaction among co-workers the higher the ability of the organization to achieve the joy of customer recipient for educational service.